GIS-Based Land Price Modelling for Housing Affordability Assessment: A Pilot Study in Volos, Greece - Panagiotis - Dimitrios Tsachageas (Critical Housing Analysis)
Land costs play a pivotal role in housing affordability but are often misrepresented in urban research. This pilot study assesses land price shifts and their implications for housing affordability in Volos, Greece, through GIS-based interpolation. Price surfaces were modelled using 2022 land plot price data and geostatistically validated to be used as a baseline. Comparison with 2024 data reveals rising land prices in areas where land was previously affordable, highlighting a growing challenge to housing affordability. This study also shows that land costs can be effectively monitored using geostatistics and price mapping, even in smaller and imperfect markets. This research contributes to the literature on spatially informed real estate analysis in less-studied areas with limited real estate data.